The influence of the metal cations and microhydration on the reaction trajectory of the N3 ↔ O2 thymine proton transfer: Quantum mechanical study - Šebesta, Filip; Brela, Mateusz Z; Diaz, Silvia; Miranda, Sebastian; Murray, Jane S; Gutiérrez‐Oliva, Soledad; Toro‐Labbé, Alejandro; Michalak, Artur; Burda, Jaroslav V (Journal of computational chemistry, 2017)
This study involves the intramolecular proton transfer (PT) process on a thymine nucleobase between N3 and O2 atoms. We explore a mechanism for the PT assisted by hexacoordinated divalent metals cations, namely Mg2+, Zn2+, and Hg2+. Our results point out that this reaction corresponds to a two‐stage process. The first involves the PT from one of the aqua ligands toward O2. The implications of this stage are the formation of a hydroxo anion bound to the metal center and a positively charged thymine. To proceed to the second stage, a structural change is needed to allow the negatively charged hydroxo ligand to the N3 proton, which represents the final product of the PT reaction. In the presence of the selected hexaaqua cations, the activation barrier is at most 8 kcal/mol. © 2017 Wiley Periodicals, Inc. Intramolecular proton transfer (PT) process on thymine nucleobase between N3 and O2 atoms is explored in presence of hexacoordinated divalent metals cations Mg2+, Zn2+, and Hg2+. This PT proceeds as a two stages process. The first step involves the PT from one of the aqua ligands toward O2. The second stage is connected with the N3‐proton ion. In the presence of the hexaaqua‐cations, the activation barrier is at most 8 kcal/mol.